Education on Anemia Prevention and Post-Supplementation Hemoglobin Examination in Students at SMAN 5 Jambi City - Ruwayda Ruwayda; Dzulfikar Djalil Lukmanul Hakim; Edhyana Sahiratmadja (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Around 468.4 million people or 30% of the population of young women and women of childbearing age (WUS) in the world are anemic. The prevalence of anemia among young women in developing countries varies between 20-70%. Recommendations from the World Health Organization (WHO) at the 65th World Health Assembly (WHA) agreed on an action plan and global targets for a commitment to reduce 50% of the prevalence of WUS anemia by 2025. (Blanket approach) that is trying to cover all targets of young women who get iron tablets and are required to consume them to prevent anemia and increase iron reserves in their bodies without prior initial screening, namely checking Hb levels. One of the high schools that was the target of the program for administering 52 iron tablets was SMAN 5. In 2022 there will be 439 students in grades 10 and 11 and 100% of them have received 52 blood tablets, but only a few have had a hemoglobin check. Giving iron tablets can increase Hb levels in patients with iron deficiency anemia, but has no effect on patients with thalassemia. The blanket approach does not separate iron deficiency anemia sufferers from other types of anemia such as thalassemia. In female students who suffer from thalassemia, giving excessive blood-boosting tablets can make the liver work harder and have no impact on increasing Hb levels. The blood supplement administration program needs to be evaluated so that it is in line with the target. This community service activity was carried out in order to evaluate the blanket approach program by examining Hb levels and screening for thalassemia in young women who had finished taking 52 tablets of iron supplement. The results of checking Hb levels and screening for thalassemia can be used as a basis for program evaluation. Furthermore, education was provided about the benefits of anemia detection and thalassemia screening in order to prepare for a healthy reproductive period.